Stres Kerja Dengan Motivasi Kerja Pada Karyawan Staf di PT. SPAA Tangerang - Nataliana, Berlian; Wijono, Sutarto (Ciencias : Jurnal Penelitian dan Pengembangan Pendidikan, 2018)
This research is aimed to know the relationship between work stress and employees work motivation. This research was applied to 68 staff employees of PT. SPAA Tangerang by using purposive sampling technique. Work stress variable was measured by Job Related Tension Index Scale by Kahn et al based on role conflict, role ambiguity, and work overload aspects (in Wijono, 2012), and work motivation variable was measured using the scale arranged by Arnolds and Boshoff (2002) based on ERG Alderfer’s theory, with existence, relatedness, and growth aspects (1969, in Wijono, 2012). The data were analyzed using Pearson product moment correlation test, and the results showed the correlation value r = -0.775 and significant value 0,120 (p > 0,05), therefore it can be concluded that there is the negative and significant correlation between work stress and work motivation of PT. Sumber Prima Anugrah Abadi Tangerang staff employees.